Sistem Monitoring Temperatur Tuang Logam dan Penggunaan Energi Berbasis IoT di MIDC - Anugrah Erick Eryantono; Muhammad Nauval Fauzi; Muhammad Fathurrohman (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Tough competition among metal casting industries requires the use of technology to produce high-quality productsandlarge quantities with optimal production costs. Parameters that affect casting products are temperature at pouring time and pouring rate. The heat loss caused by the transfer of metal through the ladle and the influence of the surrounding environment that absorbs heat can cause a significant temperature drop. Therefore, a temperature monitoring system to monitor and record the rate of temperature decrease in real-time to obtain optimal casting results is needeed, as well as a monitoring system for energy usage to reduce the cost of the production. Industrial revolution technology 4.0 in the metal casting industry,especially carbon steel and cast iron,can help operators to display data in real-time, store,process,and evaluate the data on cloud/server. This system is integrated using Internet of Things (IoT) technology. Database of casting parameters (pouringtemperature and energy usage) obtained from measurements of sensors and stored in cloud is used for analysis and evaluation of the research. The results of the monitoring system analysis was expected to help reduce production cost in MIDC.